Developments in Combustion Technology 2016
DOI: 10.5772/64747
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and Emission Characteristics of Blends: -n-Butanol- Diesel (D2); and Dual Alcohols: n-Butanol-Methanol with Gasoline in Internal Combustion Engines

Abstract: A study of the effects of oxygenated alcohol/gasoline/diesel fuel blends on performance, combustion, and emission characteristics in conventional reciprocating engines is reported. On the one hand, in alcohol-gasoline blends, dual alcohols-gasoline blends have not yet been sufficiently proven as suitable alternatives to single alcohol-gasoline blends in engines as far as performance is concerned. On the other hand, n-butanoldiesel, although it has a better miscibility factor in diesel than methanol or ethanol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Due to the reduction in delay, less portion of mixture is burned in the earlier phase of combustion. Similar results were obtained by Siwale et al, 44 Wei et al 38 and Belgiorno et al 37 All the researchers concluded that higher peaks of heat release in ternary blends of diesel/gasoline/alcohol are caused by longer ignition delay.…”
Section: Resultssupporting
confidence: 82%
“…Due to the reduction in delay, less portion of mixture is burned in the earlier phase of combustion. Similar results were obtained by Siwale et al, 44 Wei et al 38 and Belgiorno et al 37 All the researchers concluded that higher peaks of heat release in ternary blends of diesel/gasoline/alcohol are caused by longer ignition delay.…”
Section: Resultssupporting
confidence: 82%
“…Different types of compression ignition engines chamber design are used to test the mixture of n-butanol and diesel [8][9][10][11][12][13]. Some other efforts are excerted to blends more than one alcohol type with diesel and biodiesel whereas the n-butanol is mixed with biodiesel and gasoline-diesel is mixed with n-butanal and iso methanol respectively and investigated [14,16]. In this paper, 5%, 10%, 20%, and 30% (by vol%) of bio n-butanol-diesel mixtures are prepared.…”
Section: Introductionmentioning
confidence: 99%